POLA PEMANFAATAN INSTAGRAM DALAM SITUASI KRISIS PERUBAHAN KELEMBAGAAN: KOMISI PEMBERANTASAN KORUPSI DAN PERUBAHAN UNDANG-UNDANG - Venny Irliani Amanah (Jurnal Visi Komunikasi, 2020)
This research discusses the use of social media instagram KPK @KPK_RI. Social media is the fastest media in disseminating information because people can easily participate and share information using the internet network. This study uses a constructivism paradigm and qualitative descriptive by using a case study research method that aims to systematically explain a fact carefully. Data collection techniques with in-depth interviews and documentation. The pattern of using Instagram in the face of institutional crises, which leads to the statement of the leadership's attitude towards rejection of the revision of the Law which results in strategic changes in content management on Instagram @ official.kpk, the pattern of using Instagram during normal conditions and in crisis situations because it involves the content planning process until Publication gatekeeping flow adapts to demands as a channel of institutional crisis communication. In the crisis conditions of the change in the KPK law in September-October 2019, the Public Relations Bureau regulates the management strategy of Instagram @ official.kpk with a focus on content related to the revision of the KPK Law and optimizing Instagram features. Starting from live Instagram, Instagram feed, and Instagram story to provide information to the public regarding points that weaken the KPK and build relationships with the public and restore public trust.